دراسة تحليلية لأسباب الإصابات الرياضية عند لاعبي المنتخبات الوطنية تبعاً لفترات الموسم الرياضي في الأردن - مجلي، ماجد فايز; الصالح، ماجد سليم (الجامعة الأردنية - عمادة البحث العلمي, 2007)
هدفت هذه الدراسة إلى التعرف إلى أهم الأسباب المؤدية للإصابات الرياضية ونسبتها، وأكثر المناطق عرضة للإصابة وأنواع الإصابات الرياضية، كذلك التعرف إلى أكثر أنواع العلاج المستخدم عند لاعبي ولاعبات المنتخبات الوطنية الأولى تبعاً لفترات الموسم الرياضي في الأردن، وتبعاً لمتغير الجنس ونوع اللعبة والعمر التدريبي. \ استخدم الباحثان المنهج الوصفي بأسلوبه المسحي، وتكون مجتمع الدراسة من (291) لاعباً ولاعبة للموسم الرياضي 2004/2005م؛ حيث مثلت العينة ما نسبته 77.8% من مجتمع الدراسة. \ وبعد تحليل البيانات تبين أن أكثر الأسباب المؤدية إلى الإصابات الرياضية عند لاعبي المنتخبات الوطنية هو عدم القيام بالفحوصات الطبية الدورية بنسبة 8.26%، وأن هناك فروقاً ذات دلالة إحصائية لصالح الذكور ولصالح الألعاب الفردية. \ أما أكثر الإصابات الرياضية انتشاراً فكانت التقلصات بنسبة 19.40% من المجموع العام. وتبين أن الكاحل أكثر المناطق عرضة للإصابة، وبنسبة 10.60%. كما تبين أن أكثر الإصابات حدوثاً كانت في فترة الإعداد بنسبة 54.89%، وأن أكثر أنواع العلاج استخداماً هو العلاج الطبيعي بنسبة 56.10%. \ وفي ضوء النتائج أوصى الباحثان بضرورة إلزام الاتحادات الرياضية بإجراء الفحوصات الطبية الدورية للاعبين، وكذلك القيام بعمل سجل وجواز سفر طبي خاص لكل لاعب من لاعبي المنتخبات الوطنية، وضرورة توفير طبيب ومعالج متخصص لكل منتخب وطني، وتعميم نتائج هذه الدراسة على اللجنة الأولمبية والاتحادات الرياضية. This study aimed at knowing the most important causes of sports injuries and their rate as well as the major areas subject to injuries. It also aimed at knowing the kinds of injuries and the most common therapy used by the players of the national elite according to the periods of sport seasons, and to the variable of sex, kind of game and the training age. \ The scholars applied the descriptive statistical method/ survey technique. The study sample included (291) players during the sports season 2004/2005. The sample represented (77.8%) of the study community. \ The analysis of the data showed that the most causes of sport’s injuries of the players of the national elite come generally as a result of neglecting health care or ignoring periodical medical check up with a rate (8.26%). There is a statistical function for males as well as for the individual games. \ The most important kind of sport injuries of the players of the national elite were bone cramps (19.40%). \ The most organs/ areas that are subject to sport injuries among the players of national elite are the ankle injuries with a rate of (10.60%). \ The majority of sport injuries occur generally during the preparation period with a rate of (54.89%). The most common therapy followed by the players of the national elite is the natural therapy with a rate of (56.10%). \ According to the results and conclusion of this study, the scholars recommended that the sport associations should make periodical medical check up for their players. \ They suggested keeping a medical file and medical passport for each player of the national elite and stressed on the necessity of a doctor and specialized therapist to every national soccer. The results of this study should be circulated among the Olympic Committee and Sport Federations.
785002
Keywords: الألعاب الرياضية -- الأردن -- التربية الرياضية -- الإصابات الرياضية -- المنتخبات الرياضية -- المنتخبات الوطنية -- اللياقة البدنية -- الطب الرياضي -- الألعاب الجماعية -- الألعاب الفردية -- الفحوصات الطبية -- الرعاية الطبية -- الاتحادات الرياضية -- لاعبو المنتخبات الوطنية -- البرامج الرياضية -- التدريب الرياضي -- المهارات الرياضية